A Simple Compound Control Method for Flexible-link Manipulator - Sanxiu Wang; Li Yu; Jianming Xu; Kexing Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents a composite control scheme based on singular perturbation theory, which decouples the system of flexible-link manipulator into rigid motion (slow subsystem) and flexible vibration (fast subsystem) two different time scale subsystems. For the slow subsystem, a controller combined computer torque method and robust control is employed to track the desired trajectory, while, a state feedback control is used to stabilize the fast subsystem to suppress the vibration. The simulation results show that the proposed control strategy has good tracking performance and suppress the flexible-link vibration effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3515